2002
DOI: 10.1177/0013916502034002002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Distance Knowledge Using Virtual Environments

Abstract: route with more turns was overestimated. The results show that desktop virtual environments are a valid and economic research tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The survey views of the three routes resembled those of the original study by Sadalla and Magel (1980) and its replication in a virtual environment (Jansen-Osmann & Berendt, 2002;Jansen-Osmann & Wiedenbauer, 2004). They are shown in Fig.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…The survey views of the three routes resembled those of the original study by Sadalla and Magel (1980) and its replication in a virtual environment (Jansen-Osmann & Berendt, 2002;Jansen-Osmann & Wiedenbauer, 2004). They are shown in Fig.…”
Section: Methodsmentioning
confidence: 62%
“…Only in a within-participants design did 11-year-old children and adults underestimate a route with less turns in comparison with a route of equal length with more turns. This proved to be a stable finding across at least three different measurement methods: Ratio-estimation technique, route-drawing technique, and reproduction technique (Jansen-Osmann & Berendt, 2002;Jansen-Osmann & Wiedenbauer, 2004).…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, it has been suggested that both the complexity of the visual environment and rate of biomechanical effort, and visual information differences between studies, may explain why some studies using direct learning have found turn effects whereas others have not (see, e.g., Herman et al, 1986). The benefit of the new methodology is that the elimination of visual information and locomotive variation provides a pure test of a turning effect, providing confirmatory support that turning does affect memory for distance (see also Jansen-Osmann & Berendt, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Mental measurements of path lengths are often not accurate and are more often subjectively derived through other qualitative measurements. Distance in spatial representation is not encoded in terms of metric distances but in a schematic measure such as cognitive storage space, cognitive time or cognitive effort (Jansen-Osman and Berendt, 2002). Among the environmental factors, having been indicated to have a correlation with cognitive distance, the number of junctions and landmarks along the route can be referred to, increasing of which contributes to increasing the cognitive distance along the path (Sadalla and Staplin, 1980).…”
Section: Discussionmentioning
confidence: 99%